FEATURES OF THE USE OF MODERN AUTOMATED PROJECTING SYSTEMS OF MACHINE-BUILDING INDUSTRIES - RUBANKA, MYKOLA; DVORZHAK, VOLODYMYR; ZHLALI, ZHYHAD; SHCHERBAN, YURYJ; ONOFRIICHUK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The purpose of the study covered in this publication is to analyze the features of the use of modern automated projecting systems, in particular CAD/CAM/CAE technologies from the point of view of the feasibility of introducing into the technological process of manufacturing products of a machine-building enterprise. The most popular specialized integrated CAD/CAM/CAE systems of the highest category for solving design and technological problems of varying complexity are listed, the features of their use are revealed, the main advantages and disadvantages and the most significant functionality are outlined. The research used a set of general scientific approaches: visual-analytical, systematization of information, modern methods of research of mechanical systems, analysis of scientific literature and method of classification. The most important factors that directly affect the technological process of creating quality products of a modern enterprise of the machine-building industry are highlighted. The choice of the integrated cloud software platform CAD/CAM/CAE Autodesk Fusion 360 for three-dimensional modeling of machine-building industries is substantiated. Certain recommendations have been formulated for the effective use of the CAD/CAM/CAE Autodesk Fusion 360 automated projecting system in the technological processes of the engineering industry. The main specialized modules of the CAD/CAM/CAE Autodesk Fusion 360 computer-aided system are considered to solve complex problems of varying complexity. It is established that the use of modern CAD/CAM/CAE technologies can significantly reduce the complexity of technological processes of manufacturing products of machine-building industries. The scientific novelty of the performed researches is the development of engineering methods of designing a modern high-tech machine-building complex with the use of integrated CAD/CAM/CAE systems.